Efektivitas Penyidikan Tindak Pidana Peretasan (Hacking) Di Unit Cybercrime Polda Sulawesi Selatan - Wahyudi, Candra; Thalib, Hambali; Abbas, Ilham (Innovative: Journal Of Social Science Research, 2025)
This study aims to: (1) Examine, analyze, and explain the effectiveness of cybercrime investigations on hacking offenses at the Cybercrime Unit of the South Sulawesi Regional Police; (2) Identify, analyze, and explain the factors influencing the effectiveness of hacking crime investigations at the Cybercrime Unit of the South Sulawesi Regional Police. This research was conducted at the Cybercrime Unit of the South Sulawesi Regional Police using empirical research, which relies on field data as the primary source of information. The findings of this study show that: (1) The effectiveness of hacking crime investigations handled by the South Sulawesi Regional Police is less than optimal, resulting in unresolved cases; (2) The factors influencing the effectiveness of hacking crime investigations at the South Sulawesi Regional Police include legal substance, law enforcement personnel, infrastructure, public legal awareness, and legal culture. Recommendations:(1) Improvement of Law Enforcement Human Resources: Through specialized training in digital forensics and information technology. (2) International Cooperation: International coordination is necessary to effectively address cross-border cybercrimes.(3) Regulation Revision and Strengthening: Adjusting laws to keep up with technological advancements and current crime patterns.(4) Public Education: Educating the public about digital security and social media ethics.(5) Development of Cybersecurity Infrastructure: Including early detection systems and Cyber Incident Response Teams (CERT/CSIRT). Keywords: Effectiveness, Investigation, Hacking.